O-101 Elucidation of blastocyst collapse and its consequences: a comprehensive artificial intelligence-powered analysis of 1943 embryos from 643 couples. (30th June 2022) - Cimadomo, D; Marconetto, A; Innocenti, F; Trio, S; Chiappetta, V; Soscia, D; Albricci, L; Dovere, L; Giancani, A; Maggiulli, R; Erlich, I; Ben-Meir, A; et al.
Abstract: Study question: What are the causes and consequences of blastocyst collapse? Summary answer: ∼50% of blastocysts collapsed, especially if they are aneuploid and/or morphologically-poor. Yet, no impact on the live-birth-rate (LBR) per vitrified-warmed euploid single-embryo-transfer (SET) was reported. What is known already: Time-lapse-microscopy (TLM) is a powerful tool to describe the peculiar dynamics of preimplantation development. Lately, artificial intelligence (AI) has been also implemented to automatize and standardize such description. Here, we adopted AI to comprehensively portray blastocyst collapse, namely the phenomenon of embryo contraction with an efflux of blastocoel fluid and the detachment of the trophectoderm (TE) from the Zona Pellucida (ZP). Although, the causes of this event are still undetermined, small blastocyst contractions have been reported beneficial for the hatching process, while a full collapse has been associated with lower competence. Study design, size, duration: Observational study including 1943 blastocysts from 643 couples cultured in the Embryoscope between January-2013 and December-2020. TE biopsy without day3 ZP drilling and comprehensive-chromosome-testing were performed. The Fairtility® software automatically registered: (i)time of starting-blastulation (tSB), (ii)starting and ending time of each collapse (tSC and tEC), (iii)blastocysts' areas, (iv)shrinkage% [(area at SC – area at EC)/area at SC)], (v)embryo:ZP ratio at EC (area of the collapsed embryo/area of the ZP), and (vi)time of biopsy (t-biopsy). Participants/materials, setting, methods: Blastocyst quality was defined according to Istanbul Consensus (11, excellent; 12-21, good; 22-13-31, average; 33-23-32, poor) and with the Fairtility implantation score (IS) as well, i.e., a continuous variable from 0 to 1 generated by the KID+ software based on the TLM videos of preimplantation development. The main outcome was the LBR per euploid SET adjusted for confounders through logistic regressions. All couple and embryo features were also investigated for their association with blastocyst collapse. Main results and the role of chance: 47.3% of the blastocysts collapsed 1- to 9-times (interval between collapses: 4-8hr), and 73% of the couples had ≥1 collapsed blastocyst (1.8±1.1, range:1-8). No couple feature, though, was associated with blastocyst collapse. The longest collapses lasted 1.5±1.1 (0.13-5.1)hr, while the largest shrinkage% and embryo:ZP ratio at EC were 35±14% (10-78%) and 81±9% (33-90%), respectively. In ∼50-60% of collapses a 20-40% blastocyst volume reduction was registered, 40-60% or 20-40% in ∼15-30%, 60-80% in 0-4%. In case of multiple collapses, the first three involved smaller shrinkages. Blastocysts undergoing ≥1 collapse showed similar tSB as not-collapsing blastocysts, but progressively longer tEB and t-biopsy. The earlier the first event, the more the consecutive collapses. Notably, the poorer the morphology, the higher the risk (excellent, good, average, and poor not-collapsing blastocysts were 64%, 50%, 44% and 37%), number (e.g., ≥4 collapses were 0.4%, 2%, 4% and 8%) and duration (1.2±1.0, 1.4±1.0, 1.6±1.1 and 1.9±1.3hr) of blastocyst collapse. Collapsing blastocysts were significantly less euploid than non-collapsing (35% vs 47%; multivariate-OR:0.75, 95%CI 0.6-0.92, p<0.01); conversely, their LBR per euploid SET (39% vs 46%) and miscarriage rate per clinical pregnancy (17% vs 11%), were not significantly different (adjusted-OR:1.0, 95%CI 0.69-1.48, p=0.96 and adjusted-OR:1.65, 95%CI 0.79-3.42, p=0.18, respectively). All data were confirmed also by defining blastocyst quality through the Fairtility IS. Limitations, reasons for caution: Gestational and perinatal outcomes were not assessed. Other culture strategies and media shall be assessed for their association with blastocyst collapse. Perhaps, future studies from other groups and with a larger sample size might unveil a significant impact on the clinical outcomes. Wider implications of the findings: Collapse is common and delays blastocyst full-expansion. Moreover, poor morphology and aneuploidies involve a higher risk of collapse(s); however, no impact was reported on the clinical outcomes after euploid SET. AI appears to increase the throughput of the analysis, but additional data are required to research the causes of collapse. Trial registration number: Not applicable